Long-term outcome in relationship to neonatal transfusion volume in extremely premature infants: a comparative cohort study - Koopman-Esseboom Corine; van Haastert Ingrid C; Hack Karien EA; Khodabux Chantal M; von Lindern Jeannette S; van Zwieten Paul HT; Brand Anneke; Walther Frans J (BMC, 2011)
Abstract Background In premature born infants red blood cell (RBC) transfusions have been associated with both beneficial and detrimental sequels. Upon RBC transfusion, improvement in cerebral blood flow and oxygenation have been observed, while a more liberal transfusion policy may be associated with a better developmental outcome. The effect of the transfusion volume on long-term outcome is not known. Methods Observational follow-up study of a cohort of extremely premature born infants, treated in 2 neonatal intensive care units using a different transfusion volume (15 ml/kg in Unit A and 20 ml/kg in Unit B). The primary outcome was a composite of post discharge mortality, neuromotor developmental delay, blindness or deafness, evaluated at a mean corrected age (CA) of 24 months related to the transfusion volume/kg bodyweight administered during the postnatal hospital stay. Results Despite the difference in transfusion volume in clinically comparable groups of infants, they received a similar number of transfusions (5.5 ± 3.2 versus 5.5 ± 2.3 respectively in Unit A and B). The total transfused volume in unit A was 79 ± 47 ml/kg and 108 ± 47 ml/kg in unit B (p = 0.02). Total transfused RBC volume per kg bodyweight was not an independent predictor of the composite outcome (p = 0.96, OR 1.0 (CI 0.9-1.1). Conclusion There was no relationship between the composite outcome at 24 months CA and transfusion volume received during the post natal hospital stay. As there was no clinical advantage of the higher transfusion volume, a more restrictive volume will reduce total transfusion volume and donor exposure. Future research on the optimal transfusion volume per event to extreme preterm infants should include larger, prospective studies with a longer follow-up period through to childhood or even adolescence.